Surgical treatment of biliary atresia with patent distal extra hepatic bile ducts: Is hepatic portocholecystostomy the right choice? - Chandrasekharam V.V.S (Wolters Kluwer Medknow Publications, 2009)
Purpose : To report the results of surgical treatment of biliary atresia with patent distal extra hepatic bile ducts (BA with PDEBD) with special reference to hepatic portocholecystostomy (HPC) operation. Materials and Methods : The study reviews records of children operated for BA with PDEBD. The type of operation, results of surgery, postoperative course and complications during follow-up are noted. Results : Five children (mean age 83 days) underwent surgery for biliary atresia with patent extra hepatic bile ducts. The diagnosis was confirmed by intraoperative cholangiography in each case. Three children underwent HPC and two had standard hepatic portoenterostomy (HPE) as HPC was not technically feasible. The operation was considered successful in three of five children (60%, two HPC and one HPE), partially successful in one. The mean follow-up was 22 months. None of the children with HPC had cholangitis at follow-up; one child with HPE had recurrent cholangitis. Conclusions : Biliary atresia (BA) with PDEBD may be a variant with a fair chance for surgical success. When feasible, HPC may be a good treatment option in this group with acceptable results and practically no risk of postoperative cholangitis.